A study of effect of topical anaesthetics on injection pain during immunization in infants - Kumar, Magesh; Venkateshwar, V. (International Journal of Contemporary Pediatrics, 2020)
Background: Immunization is a necessary aspect of health care of children and injections are there for unavoidable. Many factors affect injection pain during immunization in infants. This study aims to see the effect of use of local anesthetics delivered by various modes for attenuation of vaccine related injection pain in infants and to compare them. Methods: An Open Label Four-Arm Randomized Control Trial of 300 healthy infants of age group 6 weeks to 6 months reported to immunization clinic for immunization with DPT-HiB-Hepatitis B combination vaccine were taken for study. The enrolled subjects were allocated into control group and intervention group (who were applied some form of local anesthesia). Results: Among the four groups of the patients studied we observed a statistical difference in the mean pain scores of the patients recorded at 15 second, 60 second and 5 min after vaccine injection (p value 0.0024 - 0.000). Group A (Infants with topical occlusive LA cream) showed minimum pain scores values at 15 second, 60 second and 5 min after vaccine injection, followed by Group C (Infants with topical LA spray with vapocoolant) whereas Control group (Infants not received any local anaesthesia) and Group B (Infants with topical LA spray without vapocoolant) exhibited the maximum pain scores. Conclusions: Topical occlusive local anesthetic cream and topical LA spray with vapocoolent, were found to be better than topical LA spray without vapocoolant or no topical anesthetic. Use of topical occlusive LA cream led to a lowest pain score. There was no significant difference in the profile of side effects following injection in the four group.